Upregulation of Scavenger Receptor BI by Hepatic Nuclear Factor 4α through a Peroxisome Proliferator-Activated Receptor γ-Dependent Mechanism in Liver - Yi Zhang; Chen Shen; Ding Ai; Xuefen Xie; Yi Zhu (PPAR Research)
Hepatic nuclear factor 4α (HNF4α) modulates the transcriptional activation of numerous metabolic genes in liver. In this study, gene-array analysis revealed that HNF4α overexpression increased peroxisome proliferator-activated receptorγ (PPARγ) greatly in cultured rat primary hepatocytes. PPAR-response-element-driven reporter gene expression could be elevated by HNF4α. Bioinformatics analysis revealed a high-affinity HNF4α binding site in the human PPARγ2 promoter and in vitro experiments showed that this promoter could be transactivated by HNF4α. The presence of HNF4α on the promoter was then confirmed by ChIP assay. In vivo, hepatic overexpression of HNF4α decreased cholesterol levels both in plasma and liver and several hepatic genes related to cholesterol metabolism, including scavenger receptor BI (SR-BI), were upregulated. The upregulation of SR-BI by HNF4α could be inhibited by a PPARγ antagonist in vitro. In conclusion, HNF4α regulates cholesterol metabolism in rat by modulating the expression of SR-BI in the liver, in which the upregulation of PPARγ was involved.